A Comprehensive Review of Viral Characteristics, Transmission, Pathophysiology, Immune Response, and Management of SARS-CoV-2 and COVID-19 as a Basis for Controlling the Pandemic - Triggle, Chris R.; Bansal, Devendra; Ding, Hong; Islam, Md Mazharul; Farag, Elmoubashar Abu Baker Abd; Hadi, Hamad Abdel; Sultan, Ali A. (Frontiers in Immunology, 2021)
COVID-19 emerged from China in December 2019 and during 2020 spread to every continent including Antarctica. The coronavirus, SARS-CoV-2, has been identified as the causative pathogen, and its spread has stretched the capacities of healthcare systems and negatively affected the global economy. This review provides an update on the virus, including the genome, the risks associated with the emergence of variants, mode of transmission, immune response, COVID-19 in children and the elderly, advances made to contain, prevent and manage the disease. Although our knowledge of the mechanics of virus transmission and the immune response has been substantially demystified, concerns over reinfection, susceptibility of the elderly and whether asymptomatic children promote transmission remains unanswered. There are also uncertainties about the pathophysiology of COVID-19 and why there are variations in clinical presentations and why some patients suffer from long lasting symptoms – “the long haulers”. To date, there is no significantly effective curative drugs for COVID-19, especially after failure of hydroxychloroquine trials to produce positive results. The RNA polymerase inhibitor, remdesivir, facilitates recovery of severely infected cases but, unlike the anti-inflammatory drug, dexamethasone, does not reduce mortality. However, vaccine development witnessed substantial progress with several being approved in various countries around the globe.